2015
DOI: 10.1103/physrevd.92.015010
|View full text |Cite
|
Sign up to set email alerts
|

MT2to the rescue: Searching for sleptons in compressed spectra at the LHC

Abstract: We propose a novel method for probing sleptons in compressed spectra at hadron colliders. The process under study is slepton pair production in R-parity conserving supersymmetry, where the slepton decays to a neutralino LSP of mass close to the slepton mass. In order to pass the trigger and obtain large missing energy, an energetic mono-jet is required. Both leptons need to be detected in order to suppress large standard model backgrounds with one charged lepton. We study variables that can be used to distingu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
0
20
1
Order By: Relevance
“…Note that the ordering of the bins in terms of signal events (as opposed to S/B) reduces the reliance on background modeling. 8 The spirit of these curves is similar to a receiving operator characteristic (ROC) curve, even though they are not technically ROC curves. 9 We verify that the procedure outlined here is not sensitive to the choice of binning.…”
Section: Preliminary Study With Uniform Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the ordering of the bins in terms of signal events (as opposed to S/B) reduces the reliance on background modeling. 8 The spirit of these curves is similar to a receiving operator characteristic (ROC) curve, even though they are not technically ROC curves. 9 We verify that the procedure outlined here is not sensitive to the choice of binning.…”
Section: Preliminary Study With Uniform Backgroundmentioning
confidence: 99%
“…This attitude is supported by the flurry of theoretical activity in recent years in designing models which "hide" the new physics from the LHC. One of the standard methods for doing so is to arrange for a "compressed" mass spectrum with a mass degeneracy of the relevant particles, such as supersymmetric (SUSY) partners, so that the resulting decay products are too soft to be triggered upon and tagged in the experimental analysis [4][5][6][7][8][9][10][11][12][13], or a "stealth" mass spectrum, where the new physics signature becomes identical to the SM background, since the additional particles are too soft to make any appreciable difference [14][15][16][17][18][19][20]. Our aim will be to highlight a kinematic variable that, either by itself or in conjunction with more conventional variables, can more effectively select signal over background when the signal spectrum is compressed and when signal events contain multi-stage cascade decays.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts were made to understand this nearly degenerate region for ∆m ≤ 20 GeV, utilizing the Vector Boson Fusion topology [5] and monojet plus dileptons [6,7], and it was found that an upper bound on the lepton transverse momentum (p T < 30 GeV) is useful for investigating this region at the LHC. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [6] also made substantial use of the kinematic variable M T 2 , which sets an upper bound on the mass of pair-produced parent particles that decay into the two visible systems (after making a specific hypothesis for the mass of the associated invisible species). The presence of the jets in both search strategies gives a transverse boost to the˜ * ˜ system, which increases the lepton momenta and the missing transverse energy in order to reduce the SM background.…”
Section: Introductionmentioning
confidence: 99%
“…The first to do so [18] used vector boson fusion and missing transverse momentum to reduce standard model backgrounds, but required around 3000 fb −1 of data. The second [19] proposed a solution remarkably similar to ours, also using a high-pT monojet to help generate E miss T and employing a moving mT2 window to distinguish signal from background. However some of the details of signal selection differ and in particular they do not address background systematics as we do in this paper using the different flavor control region.…”
Section: Toolsmentioning
confidence: 99%